Ḥȝyšš, the Egyptian Hippokampos - mythical monster or giant oarfish? - Altmann-Wendling, Victoria (The journal of Egyptian archaeology, 2023)
A serpentine god is attested on over a dozen coffins and sarcophagi dating from the Third Intermediate Period onwards. In the earliest versions, it has the head of a horse, while in later ones it appears to be a purely mythical monster. The texts identify this deity as a protective god for the deceased. New pictorial and textual sources now allow a re-evaluation of previous explanations and a new proposal for interpretation.